Proses Morfologis pada Pembentukan Nama-nama Marga Etnis Sangihe - Evi Martika D. Kasiahe; Rina P Pamantung; Leika M.V Kalangi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Sangihe ethnic surnames have numerous morphological processes, but have not been a major concern for linguists. Previous researches regarding names have not yet analyze the internal structure of a name. In this research, I analyzed names based on the lingual forms to observe that in a name, especially surname, undergoes a morphological process.The data in this research were collected through two methods, namely observation method with the technique of observing and interview with elicitation technique. This research aims to explain three things, namely morphological form, morphological processes of surnames, and the meaning of surnames. From this research, it is found that Sangihe ethnic surnames have non-affixation complex forms and trimorphemic complex forms. it is found that the same affix may produce different grammatical meaning depending on the word classes and a grammatical meaning can be produced by adding one phoneme only